Functional leaf traits of vascular epiphytes: vertical trends within the forest, intra‐ and interspecific trait variability, and taxonomic signals. (29th June 2015) - Petter, Gunnar; Wagner, Katrin; Wanek, Wolfgang; Sánchez Delgado, Eduardo Javier; Zotz, Gerhard; Cabral, Juliano Sarmento; Kreft, Holger
Summary: Analysing functional traits along environmental gradients can improve our understanding of the mechanisms structuring plant communities. Within forests, vertical gradients in light intensity, temperature and humidity are often pronounced. Vascular epiphytes are particularly suitable for studying the influence of these vertical gradients on functional traits because they lack contact with the soil and thus individual plants are entirely exposed to different environmental conditions, from the dark and humid understorey to the sunny and dry outer canopy. In this study, we analysed multiple aspects of the trait‐based ecology of vascular epiphytes: shifts in trait values with height above ground (as a proxy for vertical environmental gradients) at community and species level, the importance of intra‐ vs. interspecific trait variability, and trait differences among taxonomic groups. We assessed ten leaf traits for 1151 individuals belonging to 83 epiphyte species of all major taxonomic groups co‐occurring in a Panamanian lowland forest. Community mean trait values of many leaf traits were strongly correlated with height and particularly specific leaf area and chlorophyll concentration showed nonlinear, negative trends. Intraspecific trait variability was pronounced and accounted for one‐third of total observed trait variance. Intraspecific trait adjustments along the vertical gradient were common and seventy per cent of all species showed significant trait–height relationships. In addition, intraspecific trait variability was positively correlated with the vertical range occupied by species. We observed significant trait differences between major taxonomic groups (orchids, ferns, aroids, bromeliads). In ferns, for instance, leaf dry matter content was almost twofold higher than in the other taxonomic groups. This indicates that some leaf traits are taxonomically conserved. Our study demonstrates that vertical environmental gradients strongly influence functional traits of vascular epiphytes. In order to understand community composition along such gradients, it is central to study several aspects of trait‐based ecology, including both community and intraspecific trends of multiple traits. Abstract : Lay Summary